A Mathematical Model of Flexural-Creep Behaviour for Future Service Expectancy of a GFRP Composite Cross-Arm with the Influence of Outdoor Temperature - Alhayek A.; Syamsir A.; Supian A.B.M.; Usman F.; Najeeb M.I.; Asyraf M.R.M. (Korean Fiber Society, 2024)
Exposure to high temperatures can damage GFRP laminates mechanical properties and, as a result, degrade their long-term performance, leading to rupture during their service life. Therefore, this study investigated the flexural-creep behaviour of pultruded glass fibre-reinforced polymer (pGFRP) when subjected to elevated temperatures and utilised two mathematical models to evaluate the structure's serviceability when subjected to a variety of stress levels. Two main parameters were investigated: elevated temperature (25 to 40C) and constant load levels (12%, 24%, and 37%), whereas the pGFRP specimens were monitored for 720h (30days). Furthermore, the experimental work has been paired with mathematical models, namely, Findleys power law model and Burgers model, to predict the life span of a pGFRP cross-arm according to the data obtained from creep tests. Results showed the specimens failed in a brittle manner as expected under the static 4-point bending tests with an average ultimate strength of 242.6MPa. Moreover, both models used to simulate the creep behaviour of the GFRP laminates matched very well with the experimental data. However, these models showed a substantial difference in the strain predicted over the 120,000h period, with Burgers model predicting the specimens to reach the ultimate strain in 9.4 to 11.4years, depending on the stress level, while Findleys model only showed a minimal increase in the total strain. This suggests that Burgers model might be more conservative and more reasonable for creep at elevated temperatures. 2023, The Author(s), under exclusive licence to the Korean Fiber Society.